Forest fire and biological diversity - Nasi, Robert; Meijaard, E.; Applegate, G.; Moore, P. (2002)
Forest fires have many implications for biological diversity.This article showed the effects of forest fires on the forest ecology, the impact of human-induced or severe natural wildfire on plant diversity, effects of fire on forest fauna and effects of suppression of the natural fire regime. In forest where fire is not a natural disturbance, it can have devastating impacts on forest vertebrates and invertebrates, loss of fruit-trees results in overall decline in bird and animal species that rely on fruits for food. Deliberate human suppression of fire can also have direct negative impacts on species. However, not all species suffer from fire. Fire can have positive effects on wildlife populations in boreal forests, where fire is a major natural disturbance mechanism.